DIRECTIONS AND CONTENTS VZAYEMOPERETYNU PHILOSOPHIC-EDUCATIONAL PARADIGMS AND CONTEMPORARY BIOPOLITICS IN THE CONTEXT OF CIVIL SOCIETY. - Kostyuchkov, Sergei (Humanities Bulletin of Zaporizhzhe State Engineering Academy / Gumanìtarnij Vìsnik Zaporìzʹkoï Deržavnoï Inženernoï Akademìï, 2015)
The article defines the essence of innovative educational paradigm under the terms of a changing world, the needs and requests of rule of law and civil society. It is emphasized that new biological and particularly biopolitical knowledge and associated technologies configure the public consciousness in the production of innovative and upgraded educational and philosophical ideas. Paradigms are considered as the basic principles of cognitive activity and forms of implementation, which serve as a source of norms, standards, methods for solving problems in the field of scientific activity, therefore - setting general methodological knowledge. In the plane synergetic approach educational community characteristics becomes complicated way organized set of educational paradigms that exist therein, thereby concentrating the peculiarities inherent in this educational paradigm. Thus, within the framework of synergetic methodology is possible to build an integrative educational paradigm of the XXI century. Synergetic approach to studying and solving the problems of education and pedagogy and use definitions synergy allows to update new interpretation of the individual, which corresponds to modern philosophical and educational ideology and personality development becomes radically new content. The emergence of the twentieth century biopolitics and other bio-social and biohumanitarnyh disciplines is the result of the historical development of the life sciences; birth of biopolitics as a proper and other interdisciplinary fields of science, it was also the result of a counter human sciences and society. Biopolitics an integrated philosophical ideas and settings related to different paradigms, including a special role in its formation played idea of evolutionism and naturalism, due to historically natural-philosophical concepts of unity and spirituality in the world. It is noted that the practical achievements of modern life sciences are a real reflection of the new terms and concepts of biopolitics, hard competition shapes require optimization, storage and transmission of information, its use in educational processes, taking into account the relevance, scientific and practical importance of specific aspects of biological knowledge and, in general, - new outlook and as a result - update social life. In the development of society and a culture sotsiogeneza factors that influenced the development of the education system as a social phenomenon called diffraction kind of features that led to its entry implicitly inherent qualities of the signs and symptoms. It should be added that modern man, especially individual new domestic generation - not a passive observer, but an active actor of social and political change, a form of expression which is a course to build a progressive institution of social life, which is an association of free and equal individuals rate the development of civil society. The learning process is implemented as optimization of pure reason, the individual accumulation special, different-knowledge, defined, regulated and dosed defined public, mostly public, institutions. In terms of the first quarter of the twenty-first century as the subject of education must take a holistic, multi-dimensional person, given its necessarily complex biosocial nature in every person living person that can and should enrich knowledge and educate. The principle of the unity of man, nature and the cosmos more fully defined principles can be implemented in Humanitarian and environmental educational paradigm, the provisions of which meet the needs of co-evolutionary development of society. In the context of humanitarian and environmental educational paradigm person gets opportunities qualitative transformation of the individual-consumer educational resources to the identity of the creator-oriented constructive congeniality with the outside world society and nature. We apply in this context, the concept of "transformation" as a general vector transition from traditional society, taken in its paradigmatic dimension to society of the future.